Mid-term functional outcomes following reoperation after total ankle arthroplasty: A retrospective cohort study. Issue 8 (December 2022) - Kim, Jaeyoung; Rajan, Lavan; Fuller, Robert; O'Malley, Martin; Levine, David; Deland, Jonathan; Ellis, Scott; Demetracopoulos, Constantine
Abstract: Background: Despite a significant reported rate of non-revision reoperation after total ankle arthroplasty (TAA), it is uncertain if these subsequent procedures have an impact on the longer term outcomes. This study aimed to compare minimum five-year functional outcomes of patients who had undergone reoperation after TAA to those who did not require reoperation. Methods: Seventy-six ankles (74 patients) who underwent TAA with the Salto Talaris fixed bearing system between 2007 and 2014 were allocated into two groups based on presence (n = 16) or absence of reoperation (n = 60). Reoperations included all secondary procedures after index TAA, excluding revision surgeries requiring removal or exchange of the original prosthesis. The foot and ankle outcome score (FAOS) at preoperative and minimum five-year follow-up was compared between the groups. Additionally, improvements in FAOS subscales were compared. Preoperative deformity, postoperative implant alignment, number of periprosthetic cysts, and subsidence between groups were compared using standard weightbearing radiographs. Results: The most common cause of reoperation was gutter impingement (n = 11), followed by stress fracture of the medial malleolus (n = 2), tarsal tunnel syndrome (n = 1), periprosthetic cyst (n = 1), and infection (n = 1). In comparison to the non-reoperation group, all FAOS subscales except for the Sports and Recreational Activities subscale were significantly lower in the reoperation group at final follow-up. The reoperation group exhibited significantly less improvement in the Pain, Symptoms, and Quality of Life subscales at final follow-up (p < 0.05). There were no statistical differences in the radiographic parameters between both groups. Conclusions: Patients who underwent reoperation after TAA demonstrated inferior functional outcomes at mid-term follow-up. An emphasis should be placed on preventing possible causes of reoperations to achieve favorable patient outcomes. Additionally, if a reoperation is deemed necessary, a thorough evaluation and surgical correction of underlying causes should be achieved.